The Ubiquity of Good Taste: A Spatial Analysis of the Craft Brewing Industry in the United States - Neil Reid; Ralph McLaughlin; Michael Moore (European Regional Science Association (ERSA), 2013)
The performance and composition of the U.S. brewing industry has changed dramatically over the past three decades. The industry displays contradictory shifts in both aggregate production volume and number of firms. While aggregate beer production in the US has increased modestly, per capita production has decreased steadily since the early 1980s, dropping 26 percent between 1981 and 2011. However, the number of brewing establishments increased substantially during the same period, expanding from 48 breweries in 1981 to nearly 1,700 by 2011 ? a 3,500 percent increase. So what explains this counterintuitive story? And how has this story manifested itself over space? Much of the scholarly literature has examined the industrial structure of the brewing sector and shows the industry shifted from large-scale and oligopolistic production of a homogenous product ? American pale lager ? to a more competitive and dispersed production of a highly diversified product ? craft beer. This shift towards production of craft beer ? which is made in relatively small batches using a variety of high quality ingredients, methods, and styles ? likely mirrored an internationalization of US consumers? palates. However, analyses of how the craft beer industry has manifested itself over space are few in number. We might expect, a priori, a spatially homogenous distribution of craft beer production. This is because unlike wine and spirits, freshness of craft beer decreases relatively quickly over time without refrigeration, and transportation of beer is more expensive compared to other types of fermented beverages. Thus, ceteris paribus, the highest quality and lowest cost craft beer originates from local production. While other explanatory factors may certainly affect the geography of craft beer producers (such as state and local regulations), this need for freshness likely explains the seemingly ubiquitous appearance of hundreds of microbreweries and brewpubs across the county. The desire for craft beer on the part of consumers also reflects the interplay of a number of other factors, including the emergence of a niche market for more flavorful beers, rising incomes, and the growth of the ?buy local? movement. Here we examine (i) temporal changes in the aggregate production volume and the total number of brewing establishments for each state, (ii) state-level variation in total beer production, total craft-beer production, percent craft beer production, and per-capita craft beer production, and (iii) map the precise location of craft beer establishments to show the spatial and temporal distribution of craft breweries in the U.S.
Keywords: 330; Brewing Industry; Craft Beer; Industrial Location